Whatsapp Instant Messaging Activity in Writing English Slogans to Stimulate the 10th Grade Vocational Students’ Critical Thinking Skill - Siti Nur Kholifah Hidayati; Dedeh Rohayati; Bambang Ruby Sugiarto (Journal of English Education Program (JEEP), 2026)
The research reports on issues centred of Instant Messaging Activity in Writing English Slogans to Stimulate the 10th Grade Vocational Students’ Critical Thinking. The idea derives from the facts that students still feel writing difficult skill involving vocabulary mastery and sentences translation; this topics leads the research to be carried out. The study aims to find out the activity of using instant messaging in writing English slogans to stimulate students’ critical thinking and analyze the linguistic features, in particular, sound strategies used by the students. In this activity, students can think critically in choosing words when writing English slogans. The method used by researchers is a qualitative case study using observation, field note, a document of narrative slogans and a semi-interview. Thirty-three students from X-OTKP have participated in this research. The observation result and field notes was to be explained descriptively; and the documents of slogans was to be analyzed by using the theory of J.A. Cuddon (1998). Meanwhile, the interview result was recorded, transcribed, and interpretied. The findings indicated that, several students were able to create an interesting slogans well and correctly even though there were still some vocabulary words written incorrectly in the slogans. This might be an evidence of students’ critical thinking skill in term of Taxonomy Bloom’s applying, analyzing, evaluation, and creating; but it still needs improvement. In addition, the use of instant messaging activities were able to provide a pleasant learning atmosphere. Unfortunately, there are still some less motivated students. Therefore, future researchers are advised to learn and determine the effectiveness of instant messaging using quantitative methods.